Meeting in the Middle: The Interpretation Gap Between People and Machines - Kuzminykh, Anastasia; Rintel, Sean (CHI 2019, 2019)
Effectively bridging the fields of HCI and AI requires operationalizing what human users treat as meaningful in the stream of environmental and content information. Research has yet to systematically address the significant gap between levels of granularity and interpretation of machine labels and of human comprehension. To illustrate the problem, we provide some preliminary results from our study on using machine vision to make work meetings more inclusive, particularly for visually impaired participants.
CHI 2019 Workshop on Where is the Human? Bridging the Gap Between AI and HCI